Efficacy of a 0.5% Propolis -0.9% Pomegranate Buccal Spray Treatment Compared with 2% Miconazole Gel for Denture Stomatitis Treatment in Elderly Patients: a Randomized Clinical Trial - Yêda Parro; Danielly de Mendonça Guimarães; Herick Sampaio Muller; Eduardo Coelho; Andresa Berretta; Jessica Aparecida de Lima; David Jong; Vicente de Paulo Martins; Erica Lia (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Natural products have attracted interest as an alternative to synthetic medications for the treatment of oral diseases due to their efficacy and safety. Propolis and pomegranate extracts have both demonstrated efficacy for the treatment of denture stomatitis. However, use of the two compounds together has not been tested for this purpose. Purpose: A comparison was made of the efficacy of a commercially available propolis-pomegranate buccal spray formulation for the treatment of denture stomatitis, compared with miconazole gel, based on stomatitis lesions and Candida spp. concentrations in mouth rinses. Materials and Method: This was an experimental study, characterized as an open-label, parallel two-armed, non-inferiority randomized clinical trial. Forty elderly adults aged ≥ 60 years with denture stomatitis were randomly allocated to two groups. The patients applied a buccal spray containing 0.5% propolis and 0.9% pomegranate extracts or 2% miconazole gel, a standard treatment recommended in Brazil, to the inner surface of their dentures three times a day for 14 days. They were examined at days 1, 7, 14 and stomatitis lesions were categorized according to Newton's score. Mouth rinses were made with saline solution at days 1 and 14 and then assessed for Candida spp. Results: Both treatments reduced the Newton's score, with clinical cure rates of 75 and 40% for the miconazole and propolis-pomegranate groups, respectively. The Candida concentrations in the mouth rinse decreased significantly only in the miconazole group. Conclusion: The propolis-pomegranate spray was less effective than the miconazole treatment. However, clinical improvement was also observed in patients treated with the propolis-pomegranate buccal spray.